Generalized Domino-Driven Synthesis of Hollow Hybrid Carbon Spheres with Ultrafine Metal Nitrides/Oxides - Xu, Fei; Ding, Baichuan; Qiu, Yuqian; Dong, Renhao; Zhuang, Wanqi; Xu, Xiaosa; Han, Haojie; Yang, Jiaying; Wei, Bingqing; Wang, Hongqiang; Kaskel, Stefan (Matter, 2020)
We have demonstrated an ingenious one-pot aqueous domino-driven synthesis toward hollow hybrid spheres with ultrafine metal nitrides/oxides in hollow carbon cavity. The micelle-interfacial copolymerization is applied for shell formation, while the copolymerization-generated H+ spontaneously triggers oxometallate condensation for encapsulation. By regulating the synthetic conditions, the encapsulated metal species can be well tailored with different sizes/contents (nanocluster to several nanometers) and compositions (VN, VO, MoN, WN, bimetal-based nitrides). The ultrafine VN confined in hollow carbon exhibits excellent potassium storage performance.
CRIS-Team Scopus Importer:2022-04-14
Keywords: domino-driven synthesis; encapsulation; fast kinetics; hollow carbon spheres; hollow hybrid materials; interfacial copolymerization; MAP5: Improvement; metal nitrides/oxides; potassium-ion storage; ultrafine nanoparticles